2013
DOI: 10.3390/soc3010147
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Green: The Re-discovery of Plants and Nature’s Wisdom

Abstract: Abstract:In this article, I endeavor to recount the odd history of how we have come to perceive plants like we do, and illustrate how plants themselves perceive and sense the world and, most importantly, what they can tell us about Nature. Through examples of the ingenious ways plants have evolved to thrive, I engage the idea that our modern society is afflicted by a severe disorder known as plant blindness, a pervasive condition inherited from our forefather Aristotle and accountable for the current state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…There seems, in certain cultures, to be a philosophical disposition to undervalue plants, which some scholars have traced back to Aristotle. In his enquiries into the nature of the soul, he concluded that plants could not have anything that could be called a soul and therefore, by definition, are not alive (Gagliano, 2013;. The origin of the very words "animal" and "animate" is Latin anima, meaning breath or soul; the OED defines it as "The animating principle in living things, the soul; some part or aspect of the soul, esp.…”
Section: Philosophy and "Plantness"mentioning
confidence: 99%
“…There seems, in certain cultures, to be a philosophical disposition to undervalue plants, which some scholars have traced back to Aristotle. In his enquiries into the nature of the soul, he concluded that plants could not have anything that could be called a soul and therefore, by definition, are not alive (Gagliano, 2013;. The origin of the very words "animal" and "animate" is Latin anima, meaning breath or soul; the OED defines it as "The animating principle in living things, the soul; some part or aspect of the soul, esp.…”
Section: Philosophy and "Plantness"mentioning
confidence: 99%
“…Over time, this has resulted in a widespread condition referred to as "plant blindness" (Wandersee & Schussler, 1999), where an individual fails to notice plants or recognize their importance to the world. The implications of plant blindness are far reaching: generations of teachers and students are botanically illiterate (Hershey, 1996;Gagliano, 2013), resulting in the devaluation of plants as they relate to environmental sustainability, public health, and the economy (Tomescu, 2009;Balding & Williams, 2016). Yet plants and other photosynthetic organisms form the foundation for life on earth, and failure to acknowledge their biological significance will result in dire consequences for the health of the planet and our species.…”
Section: Introductionmentioning
confidence: 99%
“…Although articles formulating the emergence of plant studies had already begun to appear in journals such as Quanta (McGowan 2013), Mother Earth News (Angier 2013), Journal of the Fantastic in the Arts (Miller 2012), Societies (Gagliano 2013;Ryan 2012), and even the Journal for Critical Animal Studies (Houle 2011), plant studies emerged into popular culture through the publication of Michael Pollan's (2013) "The Intelligent Plant" in The New Yorker. There, Pollan reports the findings of biologists-molecular, cell, plant-confirming capacities that new materialists call agency (Coole and Frost 2010) and suggesting paradigm-shifting parallels to animal capacities as well (see Table 1).…”
Section: Plant Studies: a New Field Emergesmentioning
confidence: 99%